Determinan Perilaku Keselamatan dan Kesehatan Tenaga Medis Menggunakan Pemoderasi Risk-Taking Personality - Tatan Sukwika; Naimah Naimah; Bernard Hasibuan (Faletehan Health Journal, 2023)
During pandemic the role of health workers was increasingly important. However, the risks and work responsibilities they faced became more intense; so that, hospitals should give a special attention on the health and safety of their medical personnel. The aim of this study was to partially analyze the effects of supervision, workload, and knowledge on the safety and health behavior of medical personnel with risk-taking personality as a moderator. This associative study used simple random sampling and 86 medical staff as the samples. The data analysis method used partial least square analysis with the help of SmartPLS application. The results showed that supervision and knowledge had a significant effect with a positive relationship direction on occupational safety and health behavior. On the other hand, workload had a significant influence with a negative relationship direction towards occupational safety and health behavior. Furthermore, risk taking personality was identified to be able to weaken the influence of supervision and knowledge on occupational safety and health behavior. However, risk-taking personality was not able to moderate the effects of workload on occupational safety and health behavior.